Strengthening Enforcement in Unemployment Insurance: A Natural Experiment - Patrick Arni; Amelie Schiprowski (Institute for the Study of Labor (IZA), 2016)
Enforcing the compliance with job search obligations is a core task of conditional benefit systems like unemployment insurance (UI) or welfare. For targeted policy design, it is key to understand how the enforcement regime affects job search outcomes. This paper provides first estimates that separately identify the effects of increasing enforcement strictness in UI. As a natural experiment, we exploit a reform which induced a sharp and unanticipated increase in the probability of being sanctioned after the failure to document job search effort. Using a difference-in-differences design, we find that the probability of job finding within six months increases by 6 percentage points in response to the policy change. This effect comes at the cost of lower job stability. As a consequence, early job finders experience losses in total earnings driven by fewer months in employment within the considered post-unemployment period. We use these estimates to quantify the elasticities to changes in enforcement strictness, trading off the short-run gains (job finding) against the mid-run costs (job quality).
Keywords: J64; J65; J68; 330; unemployment insurance; job search; natural experiment; enforcement